Analisis Implementasi Transformational Leadership terhadap Motivasi Kerja Pendidik dan Tenaga Kependidikan MAN 1 Mataram - Rosdianah Rosdianah; Dwi Wahyudiati (LP2M STIT Palapa Nusantara, 2022)
This study presents the implementation of transformational leadership on the work motivation of educators and education staff at MAN 1 Mataram using a qualitative case study approach. In determining the data source, purposive sampling technique was used and the data collection technique was document analysis and in-depth interviews (indeph interviews). The research subjects are educators and education staff. The data analysis techniques used in this research are data collection, data reduction, data display, and conclusion/verification until the data is saturated. The results of this study indicate that the principal is a transformative leader with evidence that has the Idealize Influence dimension the principal has charisma so that he becomes a role model, The principal's inspirational motivation is able to become an inspiration for his followers to achieve school goals, the principal's intellectual stimulation is a visionary figure for ideas and ideas to advance educational institutions, the principal's individualized consideration listens to aspirations and treats educators and education staff humanely for the development of their institutions. Transformational leadership and work motivation are very relevant to develop an organization towards a better direction, because it not only provides organizational development but can also realize a qualified organizational capacity for every situation.